PROYEK SISTEM INFORMASI PENGELOLAAN UANG KAS TOKO TIA BUSINESS JAKARTA TIMUR - Suaib, Muhammad Daffa; Briansa, Khaleed Sheehan; Ramadhan, Satria Rizqi Iman; Nurmalasari, Nurmalasari (Journal of Information System, Applied, Management, Accounting and Research, 2025)
Efficient cash management plays a crucial role in the sustainability of MSMEs. Tia Business Store still records transactions manually using a receipt book, making it prone to errors and reporting delays. This study designed a web-based cash information system using Agile methods to improve the speed and accuracy of recording. The system includes features for income, expenses, cash report recapitulation, and login for secure access. The development process included needs analysis, interface design, system implementation, and testing using Black Box techniques. As a result, the system has been proven to simplify recording and accelerate the creation of financial reports, thereby supporting operational efficiency and more accurate decision-making.